Education Right of Women in Afghanistan After 2001 - Hashimi, Sayed Edris (Technium Social Sciences Journal, 2021)
Women in Afghanistan face difficult situations, specifically when it comes to their rights. Most of the time, male-dominated Afghan society is not supportive. One important right of Afghan women, which is their right to education, has been significantly violated. This study initially stemmed from my passion for protecting women’s rights in Afghan society and analyzing the factors that do not allow them to have access to their education right after 2001. Following that, I utilize qualitative analysis of women’s rights in Afghan society to explain the difficulties women face in a war-torn and tradition-based society where men are considered superior to women. After 2001, the U.N and the U.S. started to promote human rights in Afghanistan, and the people of the country started practicing their rights after long years of war and conflict. However, there are still cultural barriers and conflicts that prevent Afghan women from having access to education.